Cymrite As an Indicator of High Barium Activity in the Formation of Hydrothermal Rocks Related to Carbonatites of the Kola Peninsula - Sorokhtina N.V.; Chukanov N.V.; Voloshin A.V.; Pakhomovsky Ya.A.; Bogdanova A.N.; Moiseev M.M. (My University, 2008)
Cymrite, BaAl2Si2O8 · nH2O, is a rare mineral formed during low-grade dynamothermal metamorphism (T = 250–300°C, P = 1–3 kbar). Cymrite has been described from many metasedimentary ores and hydrothermal rocks. In carbonatites, it has been found for the ﬁrst time. Cymrite has been identiﬁed in the Kovdor and Seblyavr massifs, Kola Peninsula. In Kovdor, this mineral has been described from one of the hydrothermal veins cutting the pyroxenite–melilitite–ijolite complex at the Phlogopite deposit; cymrite is associated with thomsonite, calcite, and stivensite. In the Seblyavr pluton, cymrite occurs in thin veins of calcite carbonatite that cut pyroxenite contacting with ijolite. Cymrite from the Seblyavr pluton is associated with calcite, natrolite, pyrite, and chalcopyrite. The mineral is optically negative and uniaxial, with extinction parallel to elongation; ω ~ 1.607(1). According to X-ray diffraction data, cymrite from Seblyavr is monoclinic, space group P1m1; unit-cell dimensions are: a = 5.33, b = 36.96, c = 7.66 Å, β = 90°, V = 1510.55 Å3. According to the results of IR spectroscopy, in the series of samples from different massifs (in the running order Kovdor–Voishor–Seblyavr), the double-layer deformation is enhanced and accompanied by a decrease in the Si–O–Si angle and weakening of hydrogen bonds of interlayer water. The empirical formulas of cymrite calculated from electron microprobe analyses are Ba 0.93–0.95 Ca 0.01–0.02 K 0.00–0.05 Na 0.02–0.04 Al 1.97–2.01 Si 1.99–2.03 O 8 (H2O) and Ba1.00–1.02 Ca 0.00–0.01 Sr 0.00–0.01 Fe0.00–0.01 Al1.94–2.00 Si1.98–2.03 O8 (H2O) at Seblyavr and Kovdor, respectively. Cymrite from the carbonatite massifs of the Kola Peninsula was formed under hydrothermal conditions at low temperature (200–300 °C), high activity of Ba and Si, and high water pressure. At Kovdor, the mineral crystal-sonite–cymrite–calcite–stevensite. Cymrite from the Seblyavr pluton is a product of hydrothermal alteration of primary Na–K–Ba silicates of ijolite: nepheline, feldspar, and probably celsian. Natrolite replaces cymrite indicating high alkalinity of late hydrothermal ﬂuids.
Keywords: Cymrite; Kovdor massif; Seblyavr massif; Kola Peninsula